Homology Molecular Modeling - Perspectives and Applications 2021
DOI: 10.5772/intechopen.94402
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Homology Modeling for Predicting the Structures of GPCRs

Abstract: Homology modeling is one of the key discoveries that led to a rapid paradigm shift in the field of computational biology. Homology modeling obtains the three dimensional structure of a target protein based on the similarity between template and target sequences and this technique proves to be efficient when it comes to studying membrane proteins that are hard to crystallize like GPCR as it provides a higher degree of understanding of receptor-ligand interaction. We get profound insights on structurally unsolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Homology modeling investigations are employed to solve multiple challenges related to protein crystallization, thus providing a pathway to gaining higher structural insights into proteins through in-silico approaches [ 122 ]. The results presented here are recommended as the first homology structural predictions for the HanPP2C protein family, which includes HanPP2C47, HanPP2C48, HanPP2C53, HanPP2C54, HanPP2C59, and HanPP2C73.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Homology modeling investigations are employed to solve multiple challenges related to protein crystallization, thus providing a pathway to gaining higher structural insights into proteins through in-silico approaches [ 122 ]. The results presented here are recommended as the first homology structural predictions for the HanPP2C protein family, which includes HanPP2C47, HanPP2C48, HanPP2C53, HanPP2C54, HanPP2C59, and HanPP2C73.…”
Section: 0 Discussionmentioning
confidence: 99%
“…As a result of homology modeling studies, various problems associated with crystallizing proteins that play essential roles in major disease pathways are often overcome and open the door to in-silico models providing more structural insight when experimental structures are lacking. 21,22 Different studies have reported 3D-modeled structures of different proteins. [23][24][25][26] Nevertheless, to our knowledge, no study has previously studied the 3D-modeled structures of all the HIV structural and accessory proteins.…”
Section: Introductionmentioning
confidence: 99%